Resiliency management of layer poultry farm business during COVID-19 pandemic in the Yogyakarta Special Province - Suci Paramitasari Syahlani; Ni Made Ari Kusuma Dewi; Galuh Adi Insani (Universitas Sebelas Maret, 2021)
Objective: The objective of the research was to identify crises on layer poultry farms specifically in Yogyakarta Special Province during COVID-19 pandemic and investigate business resiliency management to be utilised by the farmers to deal with the situation.Methods: The research was conducted on Yogyakarta Special Province in April-October 2020 with qualitative approach method and data collection was taken using in depth interview method. Research respondents were 2 layer farmers who were also chairman of farmers association, namely Pinsar Petelur Nasional and 10 farmers purposively selected using snow-ball sampling method. Data collection was taken by face to face indepth and telephone interview and subsequently data was analysed descriptively and by using content analysis.Results: Layer poultry farmers of Yogyakarta Special Province had faced challenges on their business environment that was becoming business crisis source due to disease outbreaks, natural disasters, monetary crisis, to COVID-19 pandemic. Impacts caused by the pandemic on layer poultry industry of Yogyakarta Special Province affected market demand, distribution, egg price fluctuation and feed price, respectively. Learning through self-awareness on environmental changes and conducting community and organisation coordinations that was PPN and the adaptational management that adopted by farmers to overcome the impact of COVID-19 in business.Conclusions: Experience and endurance levels were the keys to resolve risks throughout running a farming business is important asset in conducting resiliency management in mitigating impacts of COVID-19 pandemic. Presence of community, group, and organisation networks will be usefull for the growth of capacity and opportunity of farmers in utilising novel and communication technology to negotiate with relevant farming industry stakeholders to maintain the existence of layer farmers in industry during and after the pandemic. Government supports and appropriate policy are also needed in supporting a hospitable business climate for the continuity of layer poultry farms.